POTENSI PITAVASTATIN DENGAN NANOPARTIKEL POLY(DL-LACTIDE-CO-GLYCOLIDE) (PLGA) DRUG DELIVERY SYSTEM SEBAGAI TERAPI ADJUVAN PADA PENYAKIT JANTUNG KORONER - Visakha Vidyadevi Wiguna; Abiyyu Didar Haq; Luh Gde Sri Adnyani Suari (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2022)
ABSTRACT Background: During COVID-19 pandemic, people’s mobility is decreased. This phenomenon leads to the increase of sedentary lifestyle hence increasing the risk of cardiometabolic diseases. One of the disease that has a strong connection with sedentary lifestyle is Coronary Artery Disease (CAD). CAD is the most common cardiovascular disease that causes death contributing as much as 12% of all death in the world. Percutaneous coronary intervention (PCI) therapy in the acute phase of myocardial infarct can lower the infarct area but the risk of ischemic-reperfusion injury limits its therapeutic effect. Methods: This literature review uses journal articles that are sourced from online databases such as PubMed and Google Scholar. The literature search utilized several keywords such as “pitavastatin”, “drug delivery system”, “nanoparticle”, “PLGA”, “myocardial infarction”, “ischemic-reperfusion injury”. The search yielded 34 relevant literatures which used in this literature review Discussion: Pitavastatin is a statin which possesses a significant effect on LDL-C, TG, and HDL-C. Furthermore, pitavastatin also possess cardioprotective effect on ischemic-reperfusion injury by decreasing oxidative stress and increasing intracellular antioxidant. PLGA nanoparticle is proven to increase the therapeutic effect of pitavastatin because of its ability to deliver timely and its anti-inflammatory effect. . Conclusion: Pitavastatin encapsulated by PLGA nanoparticle has the ability to prevent ischemic-reperfusion injury. Current therapeutic strategy has not been able to deliver pitavastatin into the infarct site adequately in the timely manner hence PLGA needed as drug delivery system.